Evaluation of Digital Citizenship Levels of Teachers in the Context of Information Literacy and Internet and Computer Use Self-Efficacy - COKLAR, Ahmet Naci; TATLI, Ali (Asian Journal of Contemporary Education, 2020)
This research was carried out to determine the level of digital citizenship of teachers working in different branches and institutions and to determine the relationship between digital citizenship levels and information literacy and internet-computer use self-efficacy. The sample of the study consists of 161 teachers working in a district of Gaziantep province in 2016-2017 academic years. The Digital Citizenship Scale prepared by Isman and Gungoren (2014), the Information Literacy Scale prepared by Adiguzel (2011) and the Self-Efficacy Perception Scale prepared by Sad and Demir (2015) were used in the scope of the research. As a result of the research, it was found that the digital citizenship level of teachers is at a medium level. While the digital citizenship levels of teachers do not differ according to the educational institution level, they differ according to the age range. It was determined that there was a positive, significant, and middle level relationship between teachers' digital citizenship and information literacy and internet-computer use self-efficacy levels. In terms of digital citizenship level, information literacy explains 44% of the total variance, while internet and computer self-efficacy explain 31% of the variance alone.